Play to Reduce Bullying! Role-Playing Games Are a Useful Tool for Therapists and Teachers. Issue 4 (2nd October 2021) - Bagès, Céline; Hoareau, Natacha; Guerrien, Alain
ABSTRACT: The purpose of this article is to determine the effectiveness of role-playing games (RPGs) as an intervention program to reduce bullying. Eighty-six French 6th-graders were randomly assigned to either the empathy training program involving three RPG sessions of 60 minutes or to the control condition in which students benefited from three sessions of video and discussion on the topic of school bullying. The participants completed questionnaires assessing their levels of empathy, bullying, and aggressive behavior before (pretest) and after (posttest) the three sessions of the RPGs group vs control group. The results revealed a significant increase in the level of empathy and a significant decrease in bullying and aggressive behavior for those students who participated in the RPGs group. Role-playing games could be an interesting tool for interventions in real settings with students to combat school bullying.